Fatwa and Legal Reasoning on Inheritance in Temporary Marriage: A Critical Fiqh Analysis of Sayyid Murtaḍā’s Legal Thought - Mehrabi, Zahra; Saberi, Hossein; Haeri, Mohammad Hasan (Parewa Saraq: Journal of Islamic Law and Fatwa Review, 2026)
The issue of inheritance in nikāḥ al-munqaṭiʿ/mutʿah (temporary marriage) has long occupied a significant position in both classical and contemporary Islamic jurisprudential discourse, generating diverse and often conflicting legal opinions (ārāʾ) among Muslim jurists. At the core of this debate lies the issue of whether spouses in a temporary marriage are entitled to mutual inheritance, given the contractual, time-bound, and non-permanent nature of the unions. The dominant juristic view generally denies the existence of inheritance in nikāḥ al-munqaṭiʿ unless such rights are explicitly stipulated within the marriage contract. In contrast, a less widely adopted position, most particularly attributed to Sayyid Murtaḍā, affirms the establishment of mutual inheritance between spouses in temporary marriage, provided no contractual clause explicitly negates inheritance. This view has been both supported and criticized within the juristic tradition, largely due to divergent interpretations of scriptural evidence, contractual principles, and the legal consequences arising from the marriage relationship. Therefore, this study aims to systematically examine the theoretical foundations of inheritance in temporary marriage through the analytical framework of the general theory of ʿaqd al-nikāḥ (the marriage contract). The four major juristic theories concerning inheritance in nikāḥ al-munqaṭiʿ were identified and critically mapped, outlining the doctrinal bases and methodological assumptions. An in-depth analysis of Sayyid Murtaḍā’s view was then conducted, including coherence and legal plausibility in light of the essential elements, objectives, and normative implications of marriage as a binding juridical institution. The results showed that Sayyid Murtaḍā position is closely consistent with the general contractual logic of marriage, particularly the presumption of shared marital rights and obligations unless explicitly excluded, thereby reinforcing the theoretical robustness and jurisprudential defensibility within Islamic family law.